From participants to partners: reconceptualising authentic patient engagement roles in youth mental health research. (February 2023) - Prebeg, Matthew; Patton, Megan; Desai, Riddhi; Smith, Maureen; Krause, Karolin; Butcher, Nancy; Monga, Suneeta
Summary: The value of involving people with lived experience in the research process (ie, patient engagement) is increasingly being recognised within youth mental health research. The wide-reaching benefits of patient engagement have been documented in the literature, including the empowerment of patients, improvement of research outcomes, and increased relevance of research findings. Although various models exist to guide patient engagement, there are key concepts that deserve exploration to ensure the authentic implementation of these models and development of patient roles. Our Personal View aims to: identify and discuss barriers to patient engagement roles in the context of youth mental health research; consider how key concepts of relational empowerment, fluidity, and flexibility can address some of these barriers; and provide tangible recommendations for implementing authentic patient engagement throughout the research process.